Key Technologies and Protocol Architectures in Heterogeneous Network - Hongyan Liu; Chunjing Hu; Yuan Li (Dianxin kexue)
Heterogeneous network （HetNet） is recently becoming one of the key technologies in LTE-Advanced network， because it can significantly improve spectrum efficiency and system capacity， while meeting different requirements for coverage in hotspots. The research background， term definitions and system architecture of HetNet were detailed. Furthermore， the interference problem caused by the variation in network topology， and the schemes for enhanced inter cell interference coordination （eICIC） in the 3rd generation partnership project （3GPP） standardization were focused on. Lastly， other key technologies in HetNet were also analyzed， such as self-organized network （SON）， backhaul link design， mobility management， energy saving and cognitive radio， etc. Resolutions of those aforementioned key technologies have profound guiding significance for the commercial deployment of HetNet.